2022
DOI: 10.2340/jrm.v54.3972
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Manual Diaphragm Release Technique Combined with Inspiratory Muscle Training on Selected Persistent Symptoms in Men with Post-Covid-19 Syndrome: A Randomized Controlled Trial

Abstract: Objective: To determine whether the addition of manual diaphragm release to an inspiratory muscle training programme is more effective than inspiratory muscle training alone in reducing blood pressure, dyspnoea, fatigue, and aerobic performance capacity in men with post-COVID-19 syndrome.Design: A prospective, randomized-controlled trial.Setting: Chest Disease Department, Outpatient Clinic, Cairo University, Egypt.Participants: Fifty-two men with post-COVID-19 syndrome were allocated randomly to the study and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(53 citation statements)
references
References 42 publications
0
51
0
2
Order By: Relevance
“…Six eligible studies were added together in our meta‐analysis, which all in all, resulted in 210 patients in the experimental group and 139 patients in the control group. Five studies enrolled patients with post‐COVID‐19 conditions 14–16,19,20 . Three studies included patients who had been hospitalized for COVID‐19 15,19,21 and one study included patients who had never been hospitalized for COVID‐19 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Six eligible studies were added together in our meta‐analysis, which all in all, resulted in 210 patients in the experimental group and 139 patients in the control group. Five studies enrolled patients with post‐COVID‐19 conditions 14–16,19,20 . Three studies included patients who had been hospitalized for COVID‐19 15,19,21 and one study included patients who had never been hospitalized for COVID‐19 20 .…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported significant outcomes in maximal inspiratory pressure (MIP) (Del Corral et al, 2023b; McNarry et al, 2022; Nagy et al, 2022; Nopp et al, 2022). All four studies incorporated IMST with two studies using IMST alone A recent randomized controlled trial reported a minimally clinical important difference (MCID) value of 18 cm H 2 0 for the MIP within the post-COVID-19 population in an attempt to assess whether the improvements noted in MIP are clinically meaningful (Del Corral et al, 2023b).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies did not mention or have blinding processes related to study design, leading to n/a ratings in this category (Table 1). Using the OCEBM instrument to evaluate the level of evidence for each study, six of the studies had a 1b level of evidence (Del Corral et al, 2023a;Jimeno-Almazan et al, 2023;Liu et al, 2020;McNarry et al, 2022;Nagy et al, 2022;Palau et al, 2022), three had a 2b level of evidence (Abodonya et al, 2021;Hayden et al, 2021;Nopp et al, 2022), and two had a 2c level of evidence (Hockele et al, 2022;Morgan et al, 2023) (Table 2). These relatively high levels of methodological quality led to the inclusion of these studies in the review.…”
Section: Methodological Qualitymentioning
confidence: 99%
See 2 more Smart Citations